2000
DOI: 10.1007/s002940050016
|View full text |Cite
|
Sign up to set email alerts
|

Directed deletions in the aflatoxin biosynthesis gene homolog cluster of Aspergillus oryzae

Abstract: To investigate the structure of the aflatoxin gene cluster in Aspergillus oryzae, 39 strains belonging to this species were examined for the existence of pksA, fas1A, aflR and vbs, and the results compared with those for ver-1 obtained previously. These five genes are involved in aflatoxin biosynthesis in Aspergillus parasiticus. The strains examined were categorized into three groups; group 1, having the five homologs; 2, having ver-1 and vbs; and 3, having vbs homologs. Long-PCR analysis of the regions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 23 publications
4
42
1
Order By: Relevance
“…The cypA gene is located toward the telomeric region at the beginning of the aflatoxin gene cluster. The location of the aflatoxin gene cluster in the telomeric region of A. nidulans, A. oryzae and A. flavus facilitates gene loss as well as recombination, DNA inversions, partial deletions, translocations and other genomic rearrangements (Kusumoto et al 2000;Chang et al 2005;Ehrlich et al 2005;Wong and Kenneth 2005;Carbone et al 2007). The large deletions found in the current and previous studies are consistent with these suggestions.…”
Section: Amino Acid Changesupporting
confidence: 82%
See 3 more Smart Citations
“…The cypA gene is located toward the telomeric region at the beginning of the aflatoxin gene cluster. The location of the aflatoxin gene cluster in the telomeric region of A. nidulans, A. oryzae and A. flavus facilitates gene loss as well as recombination, DNA inversions, partial deletions, translocations and other genomic rearrangements (Kusumoto et al 2000;Chang et al 2005;Ehrlich et al 2005;Wong and Kenneth 2005;Carbone et al 2007). The large deletions found in the current and previous studies are consistent with these suggestions.…”
Section: Amino Acid Changesupporting
confidence: 82%
“…This gene is involved in the regulation of aflatoxin biosynthesis (Meyers et al 1998;Ehrlich et al 1999;Chang et al 2000). Similar to the current study, the majority of atoxigenic A. flavus and A. oryzae had aflatoxin gene clusters without significant deletions (Kusumoto et al 2000;Chang et al 2005;Lee et al 2006). In these cases, atoxigenicity probably results from SNPs or small deletions in aflatoxin-cluster genes (Calvo et al 2004).…”
Section: Amino Acid Changesupporting
confidence: 74%
See 2 more Smart Citations
“…The molecular mechanisms that prevent production of aflatoxins by A. oryzae isolates have been examined only recently. Kusumoto et al (15) found that several strains of A. oryzae (groups 2 and 3) have partial deletions in the aflatoxin gene cluster. However, other A. oryzae strains (group 1) with intact aflatoxin gene clusters also were identified.…”
mentioning
confidence: 99%